Стеганографическая сеть передачи данных на основе MIMO-технологии и хаотических несущих - Васюта, К. С.; Озеров, С. В. (ХНУРЭ, 2013)
The paper presents an analysis of the specific properties of chaotic signals (processes) such as sensitivity to the in-itial values of the signal and the exponential divergence of close phase trajectories, continuous power spectrum and exponentially decaying correlation function, unpredictability over long time intervals. Based on the properties of chaotic signals and MIMO- tech-nology, synthesized version of the construction of steganographic data network system hidden command and control of opera-tional-tactical level. In the network is hidden transmission of digital information due to increasing energy and structural secrecy of the information signal, the problem is solved electromagnetic compatibility provided by the multi-channel signal mean, the problem of increasing the speed of information transfer is solved. The budget for the network radio "command post  unmanned aerial vehicle" is calculated. It was established that the ste-ganographic data network level and forming a signal processing must be realized as a software-defined radio, which allows de-pending on the transmission signal to adaptively modify the track modulation types, the output power of the transmitter channel types of signal encoding parameters spread spectrum signal, data rate, the proportion of time for transmission and reception of communica-tion channels, transmission data encryption parameters. The presented approach can be implemented with the creation of a single information and communication space in a hidden system of command and control organized by the network-centric principle. This network creates a noise field in the space formed by the set of chaotic carriers, which greatly complicates the radio intelligence at the correct classification of radiation sources.
Keywords: стеганографическая сеть; хаотические несущие; MIMO-технология; бюджет связи; шум наблюдения; скрытность